Single nucleotide polymorphisms from candidate genes associated with nematode resistance and resilience in Corriedale and Pampinta sheep in Argentina - Raschia, Maria Agustina (2021)
Selective breeding of genetically resistant animals is considered a promising strategy to face the problem of nematode resistance to anthelmintics and mitigate concerns about the presence of chemical residues in animal food products and the environment. Gastrointestinal nematode resistance is a complex, multifactorial trait related to host immunity. However, the mechanisms underlying host resistance and response to infection remain to be fully elucidated. In this context, the objective of this study was to provide insight into the chromosomal regions determining nematode resistance and resilience in Corriedale and resistance in Pampinta sheep breeds. A total of 170 single nucleotide polymorphisms (SNP) from 76 candidate genes for immune response were studied in 624 Corriedale and 304 Pampinta animals. Lambs underwent artificial or natural challenges with infective larvae mainly from Haemonchus contortus. Fecal egg counts, estimated breeding values for fecal egg counts, and rate of packed cell volume change and FAMACHA© score change over the challenge were used, when available, as indicators of host parasite resistance or resilience. Phenotype-genotype association studies were conducted and significance values obtained were adjusted for multiple testing errors. Eight SNPs, located on OARs 3, 6, 12, and 20, reached significance in Corriedale sheep under artificial challenge. Those SNP represent allelic variants from the MHC-Ovine Lymphocyte Antigen-DRA, two C-type lectin domain families, the Interleukin 2 receptor β, the Toll-like receptor 10, the Mannan binding lectin serine peptidase 2, and the NLR family, CARD domain containing 4 genes. On Pampinta lambs under natural challenge, we found three significant SNPs, located in the TIMP metallopeptidase inhibitor 3, the FBJ murine osteosarcoma viral oncogene homolog, and the Interleukin 20 receptor alpha genes, on OARs 3, 7, and 8, respectively. The results obtained herein confirm genomic regions previously reported as associated with nematode resistance in other sheep breeds, reinforcing their role in host response to parasites. These findings contribute to gain knowledge on parasite resistance and resilience in Corriedale sheep and report for the first time SNPs associated with resistance to gastrointestinal parasite infections in Pampinta breed.